The use of 35 MHz ultrasonic biomicroscopy (UBM) to assess the biometric parameters of the anterior segment in pediatric cataractous eyes - Sudarshan Khokhar; Kabita Tiwari; Aishwarya Rathod; Deeksha Rani; Venkatesh Nathiya; Saumya Kumar; Aayush Majumdar; Amar Pujari; Chirakshi Dhull (Indian Journal of Ophthalmology)
Purpose: To assess the biometric parameters of the anterior segment in pediatric cataractous eyes using 35 MHz ultrasound biomicroscopy (UBM) and investigate their relationship with age and morphology of cataracts. Methods: This is a retrospective observational study conducted at a high-volume tertiary care center. We enrolled 2344 eyes of 1392 children under 15 years old with cataracts, categorizing them into four age groups. The UBM was used to measure various parameters, including bag diameter (BD), ciliary sulcus diameter (STS), anterior chamber depth (ACD), and others. White-to-white (WTW) diameter, axial length (AL), and keratometry (Km) were also measured. Results: We found that AL, WTW, angle to angle (ATA), STS, BD, and ACD increased with age, while Km decreased, indicating corneal flattening. Lens thickness (LT) was influenced by cataract morphology, and it was noted that LT increased with age in non-cataractous eyes. Cataractous eyes had smaller measurements for several parameters compared to fellow eyes. Notably, STS and BD showed a positive linear correlation, as did WTW and STS. Using statistical analysis, we derived formulas to estimate BD from STS and WTW measurements. We observed various cataract morphologies, including zonular, nuclear, partially absorbed, intumescent, posterior plaques, and persistent fetal vasculature. Conclusion: The study highlights the utility of 35 MHz UBM in assessing anterior segment biometric parameters in pediatric cataractous eyes. This information is crucial for selecting and implanting posterior chamber intraocular lenses (PCIOLs). By using UBM measurements or the derived formulas, the study suggests that the risk of complications related to PCIOL sizing can be reduced, offering a more precise alternative to using WTW alone for this purpose.